AN OVERVIEW OF PSYCHLOGICAL PERCEPTION, PSYCHOLOGICAL DISTRESS, AND COPING STRATEGY OF YPPM AL-MUTTAQIEN TEACHERS IN BALIKPAPAN AGAINST COVID-19 PANDEMIC - Umi Maisyarah (Universitas Airlangga, 2023)
Introduction: The change of education system during COVID-19 pandemic was a big challenge for teachers. These changes can lead to exhaustion for teachers, as happened to some elementary school teachers in Banten. A long period of exhaustion can develop into psychological distress such as anxiety, stress, and depression. This psychological distress can be controlled by implementing appropriate coping strategies for each individual. This study aims to describe the psychological perceptions, psychological distress, and coping strategies of teachers of YPPM Al-Muttaqien Balikpapan city in the midst of COVID-19 pandemic. Method: This research used quantitative descriptive method with cross sectional design. The research subjects were 17 respondents who were determined using the total sampling method. The variables of the study included individual characteristics, psychological perceptions, psychological distress, and coping strategies variable. The data analysis technique was performed using univariate analysis. Result: showed that there were 15 respondents who felt anxious about the COVID-19 pandemic. From 15 respondents, 3 people experienced moderate anxiety, 1 experienced moderate stress, and 2 experienced mild depression. Of the 2 respondents who admitted that they were not worried about the COVID-19 pandemic, 1 of them experienced mild depression. As many as 58.8% of respondents tended to use the EFC (Emotion Focused Coping) coping strategy and 41.2% used the PFC (Problem Focused Coping) coping strategy. Conclusion: The sub-coping most frequently used by respondents is planful problem solving and accepting responsibility.